Effect of increasing levels of Chlorella spp. on the in vitro fermentation and methane production of a corn silage-based diet - Vargas, Juan de J; Tarnonsky, Federico; Maderal, Araceli; Fernández Marenchino, Ignacio; Podversich, Federico; Schulmeister, Tessa M; DiLorenzo, Nicolás (Revista Colombiana de Ciencias Pecuarias, 2023)
Background: Generally, the forages used in cow-calf and backgrounding cattle operations have low crude protein and high fiber concentration, limiting animal performance and increasing greenhouse gas emissions. Chlorella spp., a green micro-alga, shows promising potential to provide nutrients, especially nitrogen, to low-protein diets. However, information is limited regarding the effects of Chlorella spp. on the in vitro fermentation and methane (CH4) production of diets. Objective: To evaluate the effects of increasing inclusion levels of algae (Chlorella spp.) on ruminal in vitro fermentation profile and CH4 production of a corn silage-based diet. Methods: Incubations were conducted on three separate days using corn silage and gin trash as substrate (70:30 ratio, respectively). Treatments were control (without algae) and 1, 5, and 10% of algae inclusion in the substrate replacing the basal diet. Ruminal fluid was collected from two ruminally cannulated Angus crossbred steers fed ad libitum a corn silage and gin trash diet. Final pH, concentration of volatile fatty acids (VFA) and ammonia nitrogen (NH3-N), in vitro organic matter digestibility (IVOMD), total gas, and CH4 production were determined after 24 h of incubation. Variables were evaluated. using the MIXED procedure of SAS software, and means were compared using orthogonal polynomial contrasts. Results: Algae inclusion linearly increased (p<0.01) the IVOMD. However, the final pH and concentration of VFA and NH3-N did not differ (p>0.05) among algae levels. Molar proportion of VFA and the acetate:propionate ratio was not affected (p>0.05) by increasing algae inclusion. Finally, total gas and CH4 production were not different (p>0.05) among treatments. Conclusion: The inclusion of Chlorella spp. does not modify the ruminal in vitro fermentation profile nor the CH4 production of a corn silage-based diet.